Properties of length-apodized phase-shifted lpgs operating at the phase matching turning point - James, Stephen W.; Topliss, Stephen M.; Tatam, Ralph P. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
The characteristics of length-apodized phase-shifted fiber optic long period gratings with full and partial nanostructured coatings have been explored theoretically and experimentally. The twin rejection bands that are characteristic of length-apodized phase-shifted long period gratings are studied for a long period grating (LPG) operating at the phase matching turning point. When one half of the length of the LPG is coated, complex bandgap like structure appears within the transmission spectrum, which may be of benefit to spectral filter design and for sensing applications.
Keywords: Nanoscale coatings; optical fibre long period gratings; optical filter